2008
DOI: 10.1103/physrevb.77.205410
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and quantum well states study of Sn thin films on Sn induced Si(111)-(23×23)R

Abstract: Surface morphologies and electronic structures of Sn thin films prepared on Si͑111͒-Sn͑2 ͱ 3 ϫ 2 ͱ 3͒ R30°s ubstrate are investigated by low temperature scanning tunneling microscopy/scanning tunneling spectroscopy ͑STS͒. A typical Stranski-Krastanov growth is observed at various growth temperatures ͑95-300 K͒, and the Sn islands above wetting layers exhibit the preferential thicknesses of odd-numbered atomic layers. STS measurement shows the formation of well-defined quantum well states with an oscillation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The much larger lattice mismatch between the Si(111) substrate and the Sn-ML is responsible for the lower stability of the epitaxial growth of α-Sn on Si(111). The predicted lattice mismatch (≈18%) is in good agreement with the lattice mismatch measured experimentally (19.5%) [18]. The in-plane compression induced by the Si(111) substrate on the Sn-ML leads to a large buckling distance displacement (out of plane) of the Sn atoms compared to the unsupported Sn-ML (increasing from 0.84Å to 1.95Å).…”
Section: Geometry and Thermodynamic Stabilitysupporting
confidence: 85%
See 1 more Smart Citation
“…The much larger lattice mismatch between the Si(111) substrate and the Sn-ML is responsible for the lower stability of the epitaxial growth of α-Sn on Si(111). The predicted lattice mismatch (≈18%) is in good agreement with the lattice mismatch measured experimentally (19.5%) [18]. The in-plane compression induced by the Si(111) substrate on the Sn-ML leads to a large buckling distance displacement (out of plane) of the Sn atoms compared to the unsupported Sn-ML (increasing from 0.84Å to 1.95Å).…”
Section: Geometry and Thermodynamic Stabilitysupporting
confidence: 85%
“…The same substrate is used by Barfuss et al [16] to produce thicker strained α-Sn films that behave like 3D topological insulators. Another good lattice-matched substrate is CdTe, whose (001) surface was used by Farrow et al [17] to heteroepitaxially grow α-Sn films, but their inability to grow ultrathin films led to an α-to-β-Sn phase transformation at 70 • C. Furthermore, another study showed the growth of four-monolayer-thick α-Sn on a Si(111) substrate, despite a significant lattice mismatch (19.5%) [18]. Nevertheless, a good understanding of the effect of these substrates on the electronic and structural properties of ultrathin Sn films is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Among the single elements, tin (Sn) is the very material in which the Meissner effect was first discovered [11] but realizing ultrathin Sn in the superconductive β-phase, known as white tin [12], remains challenging. The epitaxially grown Sn in the ultrathin limit tends to fall in the α-phase instead [13], whose bulk is semi-metallic and non-superconductive.Recently, however, intensive research has been devoted to investigate the thinnest possible slice of α-tin (111)-a counterpart of graphene called stanene [14]. Stanene promises various exotic features such as highly efficient thermoelectrics [15], topological superconductivity [16], high-temperature quantum spin Hall [17] and quantum anomalous Hall effects [18].…”
mentioning
confidence: 99%
“…Thin films exhibit physical properties that are distinct from their bulk counterparts as a consequence of quantum size effects and electron quantum confinement [19][20][21][22][23][24][25]. They are a unique class of nanosystems, whose electronic properties can be easily tuned upon controlling the thickness of the film at the atomic level.…”
Section: Introductionmentioning
confidence: 99%